Features of Аpplication of a Сombined Аpproach to the Еvaluation of the Мeasurement Results Uncertainty - P. S. Serenkov; V. L. Hurevich; Т. К. Тоlochko (Приборы и методы измерений, 2020)
The article exposes description of features of the combined approach application to the evaluation of measurement results uncertainty. The aim of this work is the justification and development of new science-driven approaches to achieve maximum efficacy of measurements on the criteria "accuracy/costs" at the stated level of confidence.It provides theoretical base for correctness of combined approach to assess measurement results uncertainty. There is proposition to conventionally divide measurement process into fragments – combining objects, each from shall be considered as individual element for evaluation. It is well known that combining objects can be formed by grouping individual components (resources) of the measurement process either via separate stages of the measurement process.Correctness of such approach is based on the application of "resource" and "process" approaches as regards identification of the factors that affect the measurement results uncertainty. This article provides recommendations on selection of model or empiric approach for evaluating of particular contributions from combining objects of different types into total uncertainty of the final measurement result. In order to improve the validity of empiric approach of the criteria of sufficiency of measurement method uncertainty examination was formulated. It is recommended to evaluate the total uncertainty of the final measurement result by complexation of evaluations of particular total uncertainty of the results for all fragments according to the uncertainties distribution law.It is determined two typical cases of effective application of the combined approach to evaluation of measurement results uncertainty: method of direct measurements and method of indirect measurements. This article considers features of effective application of the combined approach for both situations providing corresponding examples. Special attention is paid to the application of the combined approach to assessing the test results uncertainty. As distinct from the measurement process realized under normal conditions, testing process includes additional external influence factors that are determined by test conditions.